TELAAH IJTIHAD MASA KINI: SEBUAH KERANGKA PRAKTIS DALAM ISTINBATH HUKUM KELUARGA ISLAM - Ulva Hiliyatur Rosida (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2022)
Ijtihad is a very important requirement for the continuity of Islamic law in the world. One of them is part of Islamic law, namely Islamic family law. The type of research used in this research is library research or literature study and the approach is qualitative research. Ijtihad is exerting all the energy and mind to issue a law from its proposition. The scope of ijtihad is that in that event or problem there is no text as the subject of discussion. And also the event or problem is nashnya not qath'i. The history of ijtihad starts from the time of the Prophet then the time of the Companions and after. The issue of closing the door of ijtihad has different views. Ijtihad at this time is absolutely necessary because technological developments are so rapid and increasingly sophisticated along with the times. Among Yusuf al-Qaradawi offers three models of contemporary ijtihad which are considered to be able to overcome the legal crisis and renewal of Islamic law, especially Islamic family law. One of the cases of this era is marriage via telephone. Ijtihad can be done collectively in this contemporary era